Expression of Inflammation-Associated MicroRNAs in Epilepsy - Leal, Bárbara (2015)
Background: Neuroinflammation appears as an important epileptogenic mechanism. MicroRNAs (miRNA) are small non-coding RNA molecules that function as post-transcriptional regulators of gene expression, controlling different biological process including immune system homeostasis and function. Evidences, both in patients and animal studies, have demonstrated an abnormal brain expression of miR-146a and miR-155 in Mesial Temporal Lobe Epilepsy (MTLE), the most refractory epilepsy type. Knowing that miR expression is very stable in biological fluids such as plasma or serum our aim was to characterize miR-146a and miR-155 expression in serum of MTLE and GGE patients. Methods: Expression levels of miR146a and RNU48 (reference gene) were quantified by Real-Time PCR in serum of 16 MTLE patients all with Hippocampal Sclerosis (6F, 8M, mean age= 44.1±11.7 years, age of onset= 13.5±10.6 years, 7 with Febrile Seizures antecedents). A group of 24 healthy individuals was used as control. Relative expression values were calculated using the 2-ΔΔCt method. Results: MTLE patients had a higher expression of miR-146a (6 fold) and miR-155 (2 fold) when compared to controls. Conclusion: Our results, although preliminary, show that miR-146a and miR-155 may be suitable biomarkers for epileptogenesis. It is thought that these miRNAs have role in fine-tuning the response to pro-inflammatory cytokines during epileptogenesis. Nevertheless its importance in epilepsy development it is yet not fully understood. The comprehension of this role may be relevant for the development of new therapeutic strategies.